2009
DOI: 10.5432/ijshs.ijshs20090002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of New Gyro-Sensor and Accelerometer Device to Estimate Physical Activity

Abstract: The purpose of this study was to assess the accuracy of a new motion sensor wristband (ViM sports memory: ViM), consisting of an accelerometer and a gyro-sensor, by comparing the accuracy with those of indirect calorimeter (IC) and a commonly used accelerometer (Lifecorder: LC). Twenty-five participants (13 males; 12 females) walked at 3.6, 4.8, and 6.0 km · h ؊1 and ran at 7.2 and 9.6 km · h ؊1 on a treadmill for 5 min. Then, another 10 males performed static stretching and hopscotch for 5 min each. Measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 31 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…The classiˆcation algorithm is based on the relationship between the amplitude of arm swing increases and walking speed (Donker et al, 2001;Ford et al, 2007;Wagenaar and van Emmerik, 2000). Takahashi et al (2009) showed that the ViM could distinguish walking speeds approximately correctly, whereas Takahashi and coworkers also reported that the accuracy of the ViM classiˆcation was inferior to that of a conventional accelerometer placed on waist. Because diŠerences in arm swing motion among individuals were larger than those of acceleration at waist, standard deviations of W1, W2, and W3 became large in the previous study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The classiˆcation algorithm is based on the relationship between the amplitude of arm swing increases and walking speed (Donker et al, 2001;Ford et al, 2007;Wagenaar and van Emmerik, 2000). Takahashi et al (2009) showed that the ViM could distinguish walking speeds approximately correctly, whereas Takahashi and coworkers also reported that the accuracy of the ViM classiˆcation was inferior to that of a conventional accelerometer placed on waist. Because diŠerences in arm swing motion among individuals were larger than those of acceleration at waist, standard deviations of W1, W2, and W3 became large in the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…In results of the previous study (Takahashi et al, 2009), there were obvious technical biases in the ViM outputs during the treadmill exercise: 1) there were few records of IR1, IR2, and IR3, because the arm swing during walking and running was a periodic rotation movement; and 2) the diŠerence between W2 and W3 became unstable among each individual, because the diŠerences in the arm swing among individuals were large at very low to moderate speeds. These biases probably resulted in problems with the calculation of regression coe‹cients of the recalibration equation.…”
Section: Data Reductionmentioning
confidence: 99%
See 3 more Smart Citations